1985
DOI: 10.1128/jcm.22.3.387-390.1985
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibiotic susceptibility testing by agar dilution and the Micro Media system (Fox Panel)

Abstract: The susceptibilities of 350 gram-positive cocci and 638 gram-negative bacilli to various antimicrobial agents were compared by using the Micro-Media system (MMS) (Fox Panel) (Micro-Media Systems, Inc., Potomac, Md.) and a standard agar dilution procedure. Major discrepancies occurred with enterococci, among which 48 of 53 isolates (91%) were found to be resistant to penicillin G by agar dilution and reported as susceptible by the MMS. Other large discrepancies occurred with Staphylococcus aureus and Acinetobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The overall observed agreements between HGMF-RES and Repliscan for AMP, SUL, and TET not only surpassed the criteria of Rand et al (23) of 0.8 for a resistance test to be considered useful but were comparable to those reported between Food and Drug Administration-approved methods (5,32). A major limitation of observed agreement as a measure of accuracy is that it does not correct for the agreement that occurs due to chance nor does it indicate a test's ability to discriminate between susceptible and resistant isolates, i.e., the test's relative specificity and sensitivity, respectively (15).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…The overall observed agreements between HGMF-RES and Repliscan for AMP, SUL, and TET not only surpassed the criteria of Rand et al (23) of 0.8 for a resistance test to be considered useful but were comparable to those reported between Food and Drug Administration-approved methods (5,32). A major limitation of observed agreement as a measure of accuracy is that it does not correct for the agreement that occurs due to chance nor does it indicate a test's ability to discriminate between susceptible and resistant isolates, i.e., the test's relative specificity and sensitivity, respectively (15).…”
supporting
confidence: 74%
“…Sensitivity and specificity are used here in the epidemiological sense and describe the proportions of isolates correctly classified by HGMF-RES as resistant and nonresistant, respectively, relative to NCCLS-accepted, designated "gold standard" tests (15). Observed agreement is a parameter that is often used to measure agreements among antimicrobial susceptibility tests (3,5,22,28,32). Degener et al (5) categorized observed agreement as follows: satisfactory, Ͼ95%; moderate, 85 to 95%; insufficient, Ͻ85%.…”
mentioning
confidence: 99%